Newly developed aggregate gradation for five asean countries - Putra Jaya, Ramadhansyah; N. E., Jasni; K. A., Masri; A. A., Mohammed; Z. F., Mohamed Jaafar; N., Mashros (IOP Publishing Ltd, 2021)
This paper presents the new aggregate gradation of the porous asphalt (PA) mixture in five Asean countries including Malaysia, Indonesia, Vietnam, Thailand and Singapore. The PA aggregate gradation need to be developed as it may suit all of the countries and the air voids content for Asean countries can be standardized. This study was carried out to investigate the air voids properties. Several aggregate testing should be conducted in order to get the new porous asphalt aggregate gradation that suits all Asean countries. Sieve analysis test was conducted to see the patterns of the aggregate gradation curve. Sieve analysis test were tested three times for each of the countries to get the best average. The results were then plotted in one graph for all countries to be evaluated. From the analysis, Singapore specification started with 0.075mm, followed by 0.15mm, 0.3mm, o.6mm and 2.36mm are seems to have all the criteria in terms of aggregate gradations for fine aggregate and the rest are from Thailand aggregate specification for lower line while for upper line, Vietnam specifications were proved to have all the criteria within all five countries gradations.